Air quality monitoring in dairy farms: Description of air quality dynamics in a tunnel-ventilated housing barn and milking parlor of a commercial dairy farm - A. Jannat; Amanda Johnson; D. Manriquez (Journal of Dairy Science, 2025)
ABSTRACT: This study aimed to describe air quality dynamics in a commercial dairy farm focusing on 2 locations: a tunnel-ventilated barn (TVB) and a milking parlor (MKP). Assessed air quality components included carbon monoxide (CO), carbon dioxide (CO2), methane (CH4), ammonia (NH3), particulate matter 2.5 µg/m3 (PM2.5), total volatile organic compounds (VOC), and temperature-humidity index (THI), which were continuously monitored from August 16 to December 22, 2023, using a multiple air quality sensor platform. Descriptive analysis revealed significant hourly variability in the air quality dynamics during the study period. Mixed-effects models revealed no significant differences in the overall CO and THI measurements between the barn and milking parlor. However, the location significantly influenced overall concentrations of other air components including CO2, CH4, PM2.5, VOC, and NH3. Overall comparisons between TVB and MKP showed that the TVB had a higher overall CO2 concentration mean during the observation period compared with the MKP (LSM ± SEM; 640 ± 9.02 vs. 612 ± 9.01 ppm), while the MKP recorded highest CH4 levels (11.03 ± 0.52 vs. 8.87 ± 0.52 ppm). In the TVB, the NH3 levels ranged from 0.401 to 44.9 ppm, whereas no NH3 was detected in the MKP. The MKP recorded higher overall PM2.5 compared with the TVB (5.51 ± 0.31vs. 3.21 ± 0.31µg/m3). The VOC levels exhibited higher overall means in the TVB compared with the MKP (153 ± 2.18 vs. 144 ± 2.16 ppm) but were characterized by substantial variability in both locations. Temporal trends suggested that the monitored air components might be influenced by farm activities such as feeding, cleaning, and milking as identifiable peaks we observed at specific hours of the day. We identified hourly pattern dynamics of CO, CO2, CH4, NH3, PM2.5, VOC, and THI within the TVB and the MKP. Understanding these dynamics provides the opportunity to develop mitigation strategies for enhancing air quality within dairy facilities.